Correction: Pathogenicity of Nosema sp.(Microsporidia) in the Diamondback Moth, Plutella xylostella (Lepidoptera:Plutellidae) - Nadia, Kermani; Zainal-Abidin, Abu-Hassan; Dieng, Hamady; Noor Farehan, Ismail; Mansour, Attia; Idris, Abd Ghani (Research Gate, 2013)
Biological control using pathogenic microsporidia could be an alternative to chemical control of the diamondback moth (DBM) Plutella xylostella (Lepidoptera: Plutellidae). The microsporidium Nosema bombycis (NB) is one of the numerous pathogens that can be used in the Integrated Pest Management (IPM) of DBM. However, its pathogenicity or effectiveness can be influenced by various factors, particularly temperature. This study was therefore conducted to investigate the effect of temperature on NB infection of DBM larvae. Second-instar larvae at different doses (spore concentration: 0, 1×102,1×103,1×104, and 1×105) at 15°, 20°, 25°, 30° and 35°C and a relative humidity(RH) of 65% and light dark cycle (L:D) of 12∶12. Larval mortality was recorded at 24 h intervals until the larvae had either died or pupated. The results showed that the spore concentration had a significant negative effect on larval survival at all temperatures, although this effect was more pronounced (92%) at 35°C compared with that at 20 and 30°C (≃50%) and 25°C (26%). Histological observations showed that Nosema preferentially infected the adipose tissue and epithelial cells of the midgut, resulting in marked vacuolization of the cytoplasm. These findings suggest that Nosema damaged the midgut epithelial cells. Our results suggest that Nosema had a direct adverse effect on DBM, and could be utilized as an important biopesticide alternative to chemical insecticides in IPM.